SPLITTING OF THE RICE HYBRIDS ACCORDING TO THE TILLERING ON THE VARIOUS LEVELS OF NITROGEN FERTILIZING - Р. I. Kostylev; A. A. Redkin; E. V. Krasnova (Зерновое хозяйство России, 2018)
The article has presented the study results of the effect of various doses of nitrogen fertilizers on the tillering of two rice varieties and the hybrid population of the fourth generation, obtained during the hybridization of ‘Lampo’x’Komandor’. In Russia, where rice is cultivated according to the technology of the direct sowing into the soil, the domestic varieties possess insufficient tillering, so we have to create a necessary density of stand due to the increased seeding rate. The method has got some advantages due to better maturation of plants and rapid harvesting, but when we disorder the soil layout, the seedlings become sparser and the productivity reduces. We can solve the problem with the fast maturing rice varieties, possessing high tillering and rapid maturation of the stem shoots. The main purpose of the work is to study the correlation of tillering with other factors of productivity, its inheritance and its expression in the various environmental and fertilizing conditions, the possibility of its combining with other economic-valuable traits to breed a productive, fast maturing rice variety with high tillering, tolerance to lodging and diseases, good quality of kernels, adapted to the local climate and soil. The parental varieties significantly differed from each other. The variety ‘Lampo’ possesses a high potential of tillering, ‘Komandor’ possesses a low one. It has been determined that nitrogen fertilizing changes the average parameters of the trait. The tillering of the studied varieties and hybrids increases on 0.76-1.36 stems/plant on average when the doses of fertilizers increase on 30 kg/ha. Thereby the increase of the doses of fertilizers doesn’t have a significant effect on the inheritance of the trait. The hybrid always occupies an intermediate position among the parental varieties. The use of the revealed regularities in the breeding work gave the possibility to breed the rice variety ‘Akustik’ with the genes of high tillering. In 2015 the variety was sent to the State Variety Testing.